Scientific Achievements of the Institute of Geography of the National Academy of Sciences of Ukraine in 2023 - Maruniak, Eu. O.; Chekhnii, V. M. (Ukrainian Geographical Journal, 2024)
The publication aims to highlight the Institute of Geography of the National Academy of Sciences of Ukraine’s main scientific achievements from research conducted in 2023. Particular attention has been paid to the restoration and development of regions and communities during the war and post-war period.